O stress ocupacional em professores do ensino médio - Orlandino, Andrea (2008)
The studies on occupational stress in the educational profession still healthy very recent and they leave countless subjects in open. This work intended to call the attention for the high prevalence of occupational stress among the professionals of the teaching, and for that, it investigated the presence of the stress among the teachers of the medium teaching, identifying their symptoms and sources. It was treated of a quanti-qualitative study of field involving 25 teachers of a school of Medium Teaching of the State Net in the city of Colorado - Paraná. The instrument of collection of the quantitative data was the adapted version and validated of the Inventory of Symptoms of Stress for Adults (ISSL) (Lipp, 2000). The methodological approaches and the results computed by this author constitute basic references for the present work. This research had for purpose to determine the main sources of occupational stress that you/they happen in teachers of the medium teaching and the intensity degrees felt by their teachers, as well as the current effects of psychosomatic nature. The resulting conclusions just refer to the population that it was extracted the sample, however his/her extension will request including studies. The derived conclusions of this study would allow to formulate pertinent recommendations to the accomplishment of new researches in this field, with extrapolation to other educational populations and no educational, as well as to the study of strategies to repeat or to lessen defined stressful factors in the present researches. He/she improved among the teachers of the public net of the medium teaching, a high index of professionals in the resistance phases and almost exhaustion, what only comes to confirm the precariousness of the work atmosphere, as the structure lack, of human resources, besides the low wages that force the professionals to support her/it an excessive workload.